APAKAH PROSES PERENCANAN PEMBANGUNAN DISNAKERTRANS KABUPATEN KULON PROGO SESUAI DENGAN UNDANG-UNDANG NO. 25 TAHUN 2004? - Junior Hendri Wijaya (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2021)
The condition of the people of Kulon Progo Regency, has faced problems and challenges in the future, and by taking into account the strategic and potential factors possessed by the community, stakeholders, and the Regency Government, the Vision of Kulon Progo Regency is as stated in the Regional RPJP of Kulon Progo Regency 2005-2025. . The purpose of this study was to determine whether the development planning process of the Department of Manpower and Transmigration of Kulon Progo Regency is in accordance with law no. 25 of 2004. The research method used is qualitative. These results indicate that the development planning process at the Manpower and Transmigration Office of Kulon Progo Regency is in accordance with Law No. 25 of 2004, this has been proven by the initial stage process starting from the preparation of the SKPD Renstra document compiled by referring to the 2017-2022 Kulon Progo Regency RPJMD which starts from planning preparation, planning determination, controlling plan implementation; and evaluation of the implementation of the plan. However, the concrete implementation is not evenly distributed in the Kulon Progo area.